Fatores determinantes do disclosure ESG em países emergentes e em regiões do Brasil: uma análise do custo da dívida e das características nível firma e nível país - Iglesias, Thayla Machado Guimarães (2023)
Based on the stakeholders, voluntary disclosure and legitimacy theories, this study investigates the determining factors of ESG (Environmental, Social and Governance) disclosure at firm and country level from the perspective of emerging countries. Furthermore, it analyzes the relationship between ESG disclosure and the cost of debt of Brazilian companies, in the context of Brazil's macro and mesoregions. It is known that studies aimed at investigating ESG criteria have grown in Brazil and around the world as ESG disclosure practices are incorporated into investment decisions (Yu & Luu, 2021). This research expands the discussions on this topic by investigating how ESG disclosures are impacted by aspects at firm and country level, in the context of emerging countries, whose growth is significant in relation to more developed countries, although they are less efficient markets and with less liquidity (Kearney, 2012). Furthermore, it focuses on analyzing the relationship between ESG disclosure and the cost of debt of Brazilian companies, as Brazil represents one of the emerging countries with the largest number of signatories to the United Nations Principles for Responsible Investments (PRI) (PRI, 2023b; Yamahaki & Frynas, 2016), in which 86% of the 100 largest Brazilian companies (N100) report sustainability reports, a value higher than the general average (79%) of the 58 countries investigated (KPMG, 2022). This study is therefore composed of two Essays, with Essay 1 focusing on understanding the influence of firm-level factors, the corruption index and legal enforcement on ESG disclosures by companies in emerging countries. Using ESG disclosure data from 19 countries in the period 2016-2021, multilevel models were estimated in a sample with 19,468 firm-year observations. It is believed that internal factors of organizations, focused especially on financial performance and the characteristics of the board of directors, as well as particularities at country level, are relevant in companies' ESG disclosures. The results signaled a positive effect of the presence of women and independent members on the board of directors and a sustainability/CSR/ESG committee on ESG disclosure, as well as showing that less corrupt countries tend to have greater ESG disclosure. Contrary to expectations, it was noted that countries with greater political rights present lower ESG disclosure and there was no significance of financial performance, CEO duality and the rule of law in ESG disclosures. Essay 2, in turn, discusses the impact of ESG disclosure on the cost of debt of Brazilian, non-financial firms, considering the effect of regionality. In a sample containing 576 firm-year observations, dynamic panel models were estimated with System GMM in one or two steps and, contrary to expectations, ESG disclosure did not show a negative and significant relationship with the cost of debt. Regarding regionality, static panels with random and pooled effects were estimated and it was found that Brazil's macro-regions are related to the cost of debt of Brazilian companies, although there was no significance in the mesoregions of Triângulo Mineiro, Alto Paranaíba and Sul Goiano with the cost of debt. Therefore, this study contributes to the literature by providing empirical evidence on the relevance of gender diversity, board independence and lower corruption rates in ESG disclosure in emerging countries, as well as the Brazilian reality regarding ESG disclosures, since in this country, the benefits that environmental, social and governance practices provide for companies, investors, creditors, as well as all stakeholders involved, when it comes to sustainable economic and social performance, are not yet noticeable.